2019
DOI: 10.1097/sap.0000000000001850
|View full text |Cite
|
Sign up to set email alerts
|

Anabolic-androgenic Steroid Use Among Gynecomastia Patients

Abstract: Background Anabolic-androgenic steroids (AAS) are widely implicated in gynecomastia development. Surgery is the definitive treatment for cases persisting after cessation of AAS use. Currently, the relevance of AAS use to the surgical approach of gynecomastia has not been well explored. This study aims to compare patient characteristics, surgical outcomes, and surgical management of gynecomastia correction in AAS users versus nonusers. Methods A retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…To prevent major bleeding and prevent revisions, meticulous intraoperative hemostasis is necessary. 24 In our hospital, we often increase the blood pressure of the patient to a high-normal level for exact hemostasis. Furthermore, drains and compression can also help.…”
Section: Discussionmentioning
confidence: 99%
“…To prevent major bleeding and prevent revisions, meticulous intraoperative hemostasis is necessary. 24 In our hospital, we often increase the blood pressure of the patient to a high-normal level for exact hemostasis. Furthermore, drains and compression can also help.…”
Section: Discussionmentioning
confidence: 99%
“…2,23 Estrogenic side effects are common due to the aromatization of exogenous androgens, causing issues such as gynecomastia. 33 Exogenous testosterone is also shown to accelerate the growth of existing metastatic prostate cancer. 34 A wide range of behavioral effects are reported with AAS use including impulsivity, hypomanic/manic symptoms, aggression, and anxiety.…”
Section: Injectable Androgenic Anabolic Steroidsmentioning
confidence: 99%
“…In the study conducted by Vojvodic et al. it was found that 11% of the patients with gynecomastia used AAS, and the patients who needed reconstructive surgery were statistically significantly more likely to be athletes using AAS [ 34 ]. These consequences, attributed to the use of AAS and its impact on physical appearance, may elucidate the observed elevated levels of depression that were associated with the estradiol levels of participants in our study.…”
Section: Discussionmentioning
confidence: 99%